2022
DOI: 10.1159/000521772
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Sublingual Bacterial Vaccine for the Prophylaxis of Recurrent Urinary Tract Infections

Abstract: <b><i>Introduction:</i></b> Recurrent urinary tract infections (rUTIs) affect 5–10% of women, resulting in an enormous healthcare and society burden. Uromune® is a polybacterial sublingual vaccine with an excellent clinical benefit in rUTI prophylaxis. This study assesses the impact of sublingual vaccination on healthcare resource use and expenditures associated with this pathology. <b><i>Methods:</i></b> A quasi-experimental, pretest-posttest, single center stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The reason for this was also the difference in sample size: 166 compared to 1104. In any case, the objective of our study was not to reach 0-1 UTIs after vaccination, but to consider that the treatment was effective when it presented 0-2 UTIs [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this was also the difference in sample size: 166 compared to 1104. In any case, the objective of our study was not to reach 0-1 UTIs after vaccination, but to consider that the treatment was effective when it presented 0-2 UTIs [2].…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli is the most common pathogen for 80% of all UTIs [1]. In the USA, more than 11 million women suffer more than one UTI per year, with a direct cost of USD 659 million [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is logical that a reduction in UTI risk would translate into decreased healthcare utilization (fewer trips to seek medical attention, fewer urine cultures, etc.,) and antibiotic cost. A recent quasi-experimental, pretest–post-test, single-center study [ 47 ] including 166 women with rUTI, vaccinated with MV140 in real-life clinical practice, prospectively assessed healthcare utilization and associated costs. Primary care physician and emergency room visits, urine cultures, ultrasound exams (and other ancillary testing), and antibiotic costs significantly decreased compared to prevaccination (all p < 0.001).…”
Section: Cost-effectiveness Of Mv140mentioning
confidence: 99%
“…Immunoprophylaxis in the form of autovaccines has been used as a strategy to prevent recurrent urinary tract infections (UTIs) in some patients and currently has the highest recommendation grade while being cost efficient [2,9,10]. Nevertheless, the recommendations are the same for both genders, even if most of the evidence was obtained in women.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reducing the number of UTIs, vaccines have the potential to also reduce the costs associated with repeat infections. In a study that compared the use of vaccines with the use of prophylactic antibiotics, it was demonstrated that per patient consumption of antibiotics, consultations, emergency room visits, and complementary exams significantly decreased, resulting in a reduction in healthcare expenditure per patient/year from mean (SD) 1001.1 (655.0) to 497.1 (444.4) EUR [10].…”
Section: Introductionmentioning
confidence: 99%